(untitled) (Journal of the College of Basic Education, 2026)
Objectives of the study: -The aim of this study to identify the features of (Eco- literature) and setting a definition of its own, in order to create a new methodological framework based on the innovative critical foundations , which will create an incubator for a new critical approach that will pave a way for itself within soft, unstable ground, which has resulted in what is known as Eco-criticism. Methodology:- This study relies on the descriptive and inductive approach, which includes tracing the roots of eco- literature after a literature that is making its way towards uniqueness and specialization, as it carries awareness and feeling of the environmental phenomena around it and opens the crucible of human thought about the necessity of sharing the universe with other environmental elements. Questions of the study:-This study poses a number of questions about the nature of this literature: What are the criteria by which we evaluate literature so that it falls under the framework of eco- literature? Have human cultures, ancient and modern, distinguished what falls under the name of eco- literature or not? If this literature exists, has it gained legitimacy and established its specificity such that its presence within general literature is established? Or are we looking at a nascent Eco- literature? Conclusion:- The study concluded that the most important condition for eco- literature is the creator’s eco- awareness and his vision towards his surroundings and environment. The second condition that must be met in literature is the idea of ​​environmental balance or Eco-justice. As for the third condition that must be met in eco- literature is the moral orientation of the.